A Commercial Gift for Charity - Adriaan R. Soetevent; Te Bao; Anouk L. Schippers (Tinbergen Institute, 2016)
Commercial firms are increasingly tying the sales of their products with donations to a charitable cause. Apart from a charitable motive, offering these charity-linked bundles could be a strategic instrument for firms to increase profits. We report the results of an experiment that investigates for different of these schemes whether they are able to increase profits net of the donation, and which donation scheme is most profitable. From a theoretical perspective, given rational agents, complete markets, and absent transaction cost, selling charity-linked bundles should not be profitable even when consumers are altruistic. We find however that sellers who donate 5% of their gross revenues or an equivalent absolute amount do attain significantly higher profits. No such effect is observed when the donation is limited to 2%. Offering charity-linked bundles considerably crowds out private donations by buyers.
Keywords: D4; L2; L31; 330; Market competition; Firm behavior; Charity-linked bundling; Charitable giving; Cause marketing